Silicose em cavadores de poços da região da Ibiapaba : papel da intervenção educativa no controle da doença - Holanda, Márcia Alcântara (1998)
Silicosis affects pit diggers in the lbiapaba Mountain Range (IMR). They are men with a mean age of 39. The circumstances that favors the pit digging activities are: 1) lack of natural water sources in the IMR 2) long periods of drought 3) lack of water supply to the population from the local water reservoir 4) lack of alternatives jobs for those men 5) governmental measures with incentives in emergency programs which encourage the manual pit digging activities in an attempt to curb the drought effects. The pit diggers who acquired silicosis had less than 10 years of silica exposure. Most of them became sick after 391,4 days of activity. A primary educational intervention was implemented to a total number of 687 pit diggers in five cities of IMR in intend to prevent silicosis. The Paulo Freire’s educational method was used it was applied to the pit diggers to make them learn about the disease and the sickening process, including how to prevent it. The pit diggers actively participated in the educational program content. This was done by person to person contact among health workers and pit diggers; by group reunions and by large popular communications. In the present study, 283 of the 687 pit diggers answered a questionary in order to evaluate the effects of the educational program on the pit diggers learning about the disease and on the pit digging activities. One hundred fifteen (40,6%) of the pit diggers known they had silicosis, 122 (43,1%) known they did not have silicosis and 46 (16,3%) did not know their diagnosis. The results indicated that the educational program was important to control the disease. The majority of the pit diggers, 277 (98,9%) believed that digging pits was related to getting silicosis This believing was not different among silicotics or non-silicotics (p=0,362). Two hundred seventy one (958%) pit diggers learned that the rock dust causes silicosis and 221 (78,1%) learned that silicosis is acquired by digging pits. The pit diggers said that person to person contact was the best way to learn about silicosis. Most of them, 241 (85,8%) interrupted digging activities. This attitude was influenced by the knowledge of their diagnosis. It was more frequent if they known they had silicosis (p=0,001). The most relevant motive to stop digging was the knowledge about the presence of the silicosis among the diggers 211 (89,1%). There was an association between stopping digging and being diagnosed as silicotic (p=0,034). Nevertheless, 174 (77,7%) wished to change theirjob activity. This was not related to their health status (p=0,831). The pit diggers who did not assimilated the educational program or did not change their attitude regarding pit digging consisted a minority. They did not realize their problem and they need further attention to assimilate an educational intervention